Optical integral field spectroscopy of intermediate redshift infrared bright galaxies. Issue 4 (2nd May 2019) - Pereira-Santaella, M; Rigopoulou, D; Magdis, G E; Thatte, N; Alonso-Herrero, A; Clarke, F; Farrah, D; García-Burillo, S; Hogan, L; Morris, S; Rodrigues, M; Huang, J-S; et al.
Abstract: The extreme infrared (IR) luminosity of local luminous and ultraluminous IR galaxies (U/LIRGs;11 L_IR / L_12 andL_IR / L_ 12, respectively) is mainly powered by star formation processes triggered by mergers or interactions. While U/LIRGs are rare locally, at z > 1, they become more common, dominate the star formation rate (SFR) density, and a fraction of them are found to be normal disc galaxies. Therefore, there must be an evolution of the mechanism triggering these intense starbursts with redshift. To investigate this evolution, we present new optical SWIFT integral field spectroscopic H α + [N ii ] observations of a sample of nine intermediate- z (0.2 < z < 0.4) U/LIRG systems selected from Herschel 250 μ m observations. The main results are the following: (a) the ratios between the velocity dispersion and the rotation curve amplitude indicate that 10–25 per cent (1–2 of 8) might be compatible with being isolated discs, while the remaining objects are interacting/merging systems; (b) the ratio between un-obscured and obscured SFR traced by H α and L IR, respectively, is similar in both local and these intermediate- z U/LIRGs; and (c) the ratio between 250 μ m and the total IR luminosities of these intermediate-z U/LIRGs is higher than that of local U/LIRGs with the same L IR . This indicates a reduced dust temperature in these intermediate- z U/LIRGs. This, together with their already measured enhanced molecular gas content, suggests that the interstellar medium conditions are different in our sample of intermediate- z galaxies when compared to local U/LIRGs.